DETERMINASI KEPATUHAN PAJAK UMKM: PERAN PEMAHAMAN, KEMUDAHAN, DAN SANKSI PERPAJAKAN - Afiyah, Tatu Hayatul; Arisa, Lisa; Pratiwi, Esti Utami (Pascasarjana Universitas Sultan Ageng Tirtayas, 2024)
This research aims to analyze the influence of tax understanding, ease of tax payment, and tax sanctions on the tax compliance of MSME (Micro, Small, and Medium Enterprises) taxpayers in Serang City. This study uses a quantitative approach with a survey method. The research sample consists of 40 MSME respondents selected using purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS 26. The results show that tax sanctions have a significant effect on MSME taxpayer compliance, while tax understanding and ease of tax payment do not have a significant influence. These findings indicate that the implementation of strict sanctions can improve taxpayer compliance, whereas tax understanding and ease of tax payment need to be strengthened through other strategies such as more effective tax education and socialization. Therefore, more optimal policies are needed to enhance tax awareness and compliance among MSMEs in order to support sustainable tax revenue..